2008
DOI: 10.1590/s2179-83972008000100012
|View full text |Cite
|
Sign up to set email alerts
|

Implante contemporâneo de stents convencionais: comparação dos stents de hastes finas de aço inoxidável versus cromo-cobalto

Abstract: Contemporary Bare Metal Stents Implantation: Comparison of Stainless Steel versus Cobalt Chromium Coronary Stents Introduction: Higher strut thickness of coronary bare metal stents is associated with restenosis risk after bare metal stent implantation. New bare metal stents with thin struts have been developed, but there have been few studies comparing these new devices. Methods: from February 2004 until January 2007, 475 consecutive patients underwent percutaneous coronary intervention treating "de novo" coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Drug anchoring by physical methods (e.g., electrospinning, negative pressure, and lyophilization) enable the exclusion of polymers during drug-eluting stent fabrication. Of course, it has been reported that the thickness of the stent strut affects various pathological outcomes [ 27 ]. However, in this study, only the surface properties of the material were studied.…”
Section: Discussionmentioning
confidence: 99%
“…Drug anchoring by physical methods (e.g., electrospinning, negative pressure, and lyophilization) enable the exclusion of polymers during drug-eluting stent fabrication. Of course, it has been reported that the thickness of the stent strut affects various pathological outcomes [ 27 ]. However, in this study, only the surface properties of the material were studied.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence has suggested that patients treated with thin strut stents (<100 µm thick) show less neointimal proliferation and better outcomes than patients treated with stents with thicker struts. In the national registry, Salles et al (2008) 21 assessed the rate of target vessel revascularization, hospital stay and mean 18-month patient follow-up with the contemporary thin strut cobalt–chromium stents (Driver, Medtronic, United States - World Headquaters, 710 Medtronic Parkway, Minneapolis, MN 55432-5604) and stainless steel (Liberté, Boston Scientific) stents and observed no significant statistically differences between them.…”
Section: Discussionmentioning
confidence: 99%